Survey of the environmental impacts of pond fish farming - Gál, Dénes; Kerepeczki, Éva; Szabó, Pál; Pekár, Ferenc (Acta Agraria Debreceniensis, 2006)
The aim of this study was to survey the nitrogen, phosphorus and organic matter loads and the discharge of fishponds. The inputs and outputs of nutrient amounts of fishponds and their sources are described. The impact of a fishpond on the nutrient loads of receiver waters was determined. The investigations of this study were to determine and evaluate the nitrogen, phosphorus and organic matter budget of fishponds representing different technologies and areas.